Surface Defect Segmentation Algorithm of Steel Plate Based on Geometric Median Filter Pruning - Hao, Zhiqiang; Wang, Zhigang; Bai, Dongxu; Tong, Xiliang (Frontiers in Bioengineering and Biotechnology, 2022)
Due to problems such as the excessive amount of detection model parameters and the difficulty of applying them to factory embedded device applications. This paper focuses on the analysis of different existing deep learning model compression algorithms and proposes a model pruning algorithm based on geometric median filtering for structured pruning and compression of defect segmentation detection networks on the basis of structured pruning. Through several experimental comparisons and optimizations, the structured pruning algorithm can greatly reduce the network parameters and computational effort, and achieve the purpose of effective pruning of the surface defect detection algorithm for steel plates.